The College of Podiatry Annual Conference 2015: meeting abstracts. Issue 1 (April 2016) - Tong, Jasper; Kong, Veni; Sze, Lily; Gale, Susie; Veto, John; McArdle, Carla; Tunprasert, Thanaporn; Bradley, Victoria; Strike, Siobhan; Tunprasert, Thanaporn; Bradley, Victoria; Strike, Siobhan; et al.
Table of content P3 Medial longitudinal arch development of school children Jasper W.K. Tong, Veni P. Kong P4 Is measuring the subtalar joint reliable? Lily Sze, Susie Gale, John Veto, Carla McArdle P5 Comparison of turning gait biomechanics between able-bodied and unilateral transtibial amputee participants Thanaporn Tunprasert, Victoria Bradley, Siobhan Strike P6 Comparison of walking gait biomechanics between able-bodied and unilateral transtibial amputee participants using a new model of energy-storage-and-return (ESAR) prosthetic Thanaporn Tunprasert, Victoria Bradley, Siobhan Strike P7 An observational study of in-shoe plantar and dorsal pressures of skilled downhill skiers on a dry ski slope Robert Ashford, Roozbeth Naemi, Nachiappan Chocklingam, Xavi de Blasc P8 If the shoe fits: a footwear choice toolkit informed by social science methodologies Lisa Farndon, Vicki Robinson, Emily Nicholls P9 The identification of emotions from gait Tabitha Birch, Ivan Birch P11 Experience of foot problems in patients with systemic lupus erythematosus Simon Otter, Sunil Kumar, Peter Gow, Nicola Dalbeth, Michael Corkill, Kevin Davies, Sam Panthakalam, Maheswaran Rohan, Keith Rome P14 Negative pressure wound therapy for the management of foot wounds in the diabetic population: a review of the literature Chloe Egan, Lisa Chandler P15 Lower limb vascular assessment in diabetes: a multifaceted assessment of objective screening techniques Peta Tehan, Vivienne Chuter, Jennifer Sonter, Sean Lanting P16 Improving outcomes for diabetes foot complications Lorna Hicks P17 Acupuncture… an alternative or adjunctive treatment option for diabetes-related neuropathic pain? Christopher Joyce, David Watterson, Caroline McIntosh P18 "My back is in agony" – A cross-sectional study into the relationship between musculoskeletal complaints and a whole body postural risk assessment in podiatry students Christopher Joyce, Nigel Roberts P19 Swabs of the treatment couches: Does the material type and texture of podiatric treatment couches increase microorganism contamination? Jacqueline Forss, Chrystalla Charalambous, Jack Kirby, Oluwakemi Ojo P20 Does increased exudate viscosity effect the absorption rate of exudate into four different wound dressings? Jacqueline Forss, Sarah Caukill, Jacqueline Capon, Radiance Fong, Louis Loy P21 An investigation into the microbial load of a 40 °C and 60 °C wash Matthew Diment, Madeleine Murray, Mairghread Ellis, Carla McArdle P23 The sensitivity and specificity of the toe brachial index in detecting peripheral arterial disease: a systematic review and meta-analysis Peta Tehan, Vivienne Chuter, Christopher Oldmeadow P24 Medicines management activities and non-medical prescribing within podiatry and physiotherapy: an integrative review of the literature Nicola Carey, Karen Stenner, Heather Gage, Jane Brown, Peter Williams, Simon Otter, Ann Moore, Jude Edwards, Freda Mold, Molly Courtenay A7.2 Non-invasive vascular assessment in the foot with Diabetes: Diagnostic accuracy of ankle brachial index, toe brachial index and continuous wave Doppler Peta Tehan, Alan Bray, Vivienne Chuter A7.5 The efficacy of dressings on post nail surgery phenolised wounds Pamela Hindmoor B7.1 Cross-sectional study investigating the role of proximal and distal factors in the development of patellofemoral joint pain Craig Gwynne, Sarah Curran B7.2 Podiatrist's interpretation and use of evidence in MSK practice Andy Bridgen B7.4 Predictors of falling in older podiatry patients – findings from the REFORM study Caroline Fairhurst, Dr Joy Adamson, Belen Corbacho Martin, Sarah Cockayne, Prof Catherine Hewitt, Kate Hicks, Anne-Maree Keenan, Lorraine Loughrey-Green, Hylton Menz, Anthony Redmond, Sara Rodgers, Jude Watson, David Torgerson, Robin Hull, Sarah Lamb, Caroline McIntosh, Wesley Vernon, Lisa Farndon B7.5 The REFORM study: Insole preference, requirements and compliance of podiatry patient's aged 65 and over and at risk of falling Lorraine Loughrey-Green, Sarah Cockayne, Anthony Redmond, Anne-Maree Keenan, Sara Rodgers, Lisa Farndon, Wesley Vernon, David Torgerson, Caroline Fairhurst, Jude Watson, Hylton Menz, Sarah Lamb, Robin Hull B7.6 A podiatry intervention to reduce falls in care home residents is feasible and demonstrates benefits: results from PIRFECT, a feasibility randomised controlled trial Gavin Wylie, Zoe Young, Brian Williams, Frank Sullivan, Hylton Menz, Simon Ogston, Jacqui Morris C7.1 A survey exploring footwear habits in people with stroke and people with Parkinson's Cathy Bowen, Dorit Kunkel, Mark Cole, Margaret Donovan-Hall, Ruth Pickering, Malcolm Burnett, Dan Bader, Judy Robison, Louis Mamode, Ann Ashburn C7.2 Painful foot osteoarthritis; a common symptom in a common pathology? Peter McQueen, Maxine Daniels, Michael Doherty, Nigel Arden, Cathy Bowen C7.4 Clinical diagnosis of symptomatic forefoot neuroma in the general population: Delphi based recommendations Charlotte Dando, Lindsey Cherry, Cathy Bowen C7.5 The development and implementation of a Clinical Quality Improvement Framework suitable for use in community services Nichola Stefanou C7.6 The REFORM study - methodological considerations in running a cohort randomised controlled trial within a podiatry patient caseload Sarah Cockayne, Joy Adamson, Caroline Fairhurst, Catherine Hewitt, Anne-Maree Keenan, Sally Lamb, Lorraine Loughrey-Green, Caroline McIntosh, Hylton Menz, Anthony Redmond, Sara Rodgers, Wesley Vernon, Jude Watson, Lisa Farndon, Belen Corbacho, Robin Hull, David Torgerson A31 Jewel in the crown: Exploring the factors contributing to the development and impact of foot problems in Systemic Sclerosis (SSc) Begonya Alcacer-Pitarch, Anthony Redmond, Maya Buch, Anne-Maree Keenan